Measures of state support for the implementation of information modelling technologies in Russia - T. N. Kisel (Vestnik MGSU)
Introduction. The relevance of the study is due to the current preparation of the construction industry in Russia for the introduction of a mandatory requirement for the use of building information modelling (BIM) when working with objects financed from the budget. Such a requirement was supposed to come into force in 2022, but due to a number of circumstances, it was postponed. The article presents the results of the study, the purpose of which was to identify the opinions of representatives of the investment and construction sector on the main directions of state support of BIM implementation with the determination of the relationship between the opinions of respondents and the type of activity of their organizations. The results of the study will help to concentrate efforts on those that the industry needs the most. Identification of the respondents’ opinion in the context of the type of activity of their organizations will provide an opportunity for targeted application of state support measures in relation to those types of organizations that need them most urgently.Materials and methods. Primary data for the study were collected by survey (questionnaire) and processed using the factor analysis method. At the same time, the type of activity of their organizations was chosen as a factor potentially influencing the opinion of respondents.Results. The results of the analysis of respondents’ assessment of the effectiveness of measures of state regulation of the BIM implementation in general for the entire sample are presented. Based on the division of respondents into groups by type of activity, a factor analysis to assess the effectiveness of measures of state regulation of the BIM implementation was carried out. An assessment of the most significant state support measures in our days for the BIM implementation was made The analysis was carried out both for the sample as a whole and for groups of respondents. The analysis revealed that different groups of respondents prefer different support measures.Conclusions. It was found that the type of activity of the respondent’s organization has a significant impact on their opinion on the effectiveness of the state policy measures implemented by the time of the survey, as well as on the most timely and necessary measures that need to be implemented at present.